2018
DOI: 10.12816/0049746
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alendronate Treatment on Salivary Levels of Osteoprotegrin and TNF-α in Postmenopausal Woman with Osteoporosis and Periodontal Diseases

Abstract: Background: All diseases concerning bone destruction such as osteoporosis and periodontal diseases share common pattern in which the osteoclast cells are absolutely responsible for bone resorption that occurred when osteoclast activity exceeds osteoblast activity. Osteoprotegrin (OPG) considered as novel soluble decoy receptor known as “bone protector” since it prevents extreme bone resorption through inhibition of differentiation and activity of osteoclast by competing for binding site. It binds to receptor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…As regards inflammatory indices, in agreement with our results, many studies have shown that the cells most sensitive to bisphosphonates are those of the monocyte/macrophage system, in which osteoclasts are included. It has been reported that bisphosphonates inhibit monocyte/ macrophage migration, suppress antigen presentation by cells of the monocyte/macrophage lineage, and inhibit the production of a variety of bone-resorbing cytokines, including TNFα [61]. Moreover, Corrado et al, [62] reported the CRP-reducing effect of alendronate in various experimental animal models and in human studies.…”
Section: Plos Onementioning
confidence: 99%
“…As regards inflammatory indices, in agreement with our results, many studies have shown that the cells most sensitive to bisphosphonates are those of the monocyte/macrophage system, in which osteoclasts are included. It has been reported that bisphosphonates inhibit monocyte/ macrophage migration, suppress antigen presentation by cells of the monocyte/macrophage lineage, and inhibit the production of a variety of bone-resorbing cytokines, including TNFα [61]. Moreover, Corrado et al, [62] reported the CRP-reducing effect of alendronate in various experimental animal models and in human studies.…”
Section: Plos Onementioning
confidence: 99%